Prevalencia de helmintos enteroparásitos zoonóticos y factores asociados en Caninos Domésticos (canis familiaris) en el Barrio San Bartolomé de la Parroquia San Juan de Pastocalle. - Coello Valdiviezo, Karina Rocío (2018)
The present investigation was carried out in the San Bartolomé neighborhood of the San Juan de Pastocalle parish of the Canton of Latacunga, at present no previous studies have been carried out on the prevalence of enteroparasitic helminths in the canine population of this sector, from this perspective the the need to carry out such research, with the primary objective of determining the prevalence of zoonotic enteroparasite helminths and associated factors in the rural sector of San Bartolomé. The study was conducted on 75 randomly selected domestic canines, the coproparasitic analysis was done by the flotation method with Zinc Sulphate at 33%. Data were collected from the domestic canines through a clinical file and a survey made to each owner, about the environment where the domestic canine lives, type of floor, deworming, type of feeding and as age variable to determine the parasitic load of where the prevalence formula was used in each of the results obtained. The prevalence was 88% for parasitosis, the predominant parasite was Uncinaria stenocephala 38%, Ancylostoma caninum 34%, Toxocara canis 28% and in the survey the associated factors were evidenced as the following: never had veterinary control 81%, eating habits 77%, frequency of stool cleaning with 51%, Domestic canine coexistence 41%, land area where the canine 37% rests. These data were socialized with the inhabitants of the community of San Bartolomé neighborhood to raise awareness of the forms of contagion of enteroparasites, animal care and welfare. Once the prevalence was obtained, the social impact on responsible ownership of domestic and environmental canines was identified in terms of feces management and deworming calendar.